Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Apotek Rafa Farma 2 Surabaya - Mayang Puspita Amara; Harsono Teguh; Achmad Daengs GS (Jurnal Pengabdian Masyarakat, 2024)
A pharmacy is a type of retail business whose commodities or goods traded consist of pharmaceutical supplies, which include medicines and medicinal ingredients, as well as health supplies. A pharmacy is also a specific place where pharmaceutical work is carried out and distribution of pharmaceutical supplies and other health supplies to the public. Pharmacies have two uses, namely in providing health services and in business/competition. In line with the development of science and technology in the pharmaceutical sector, there has been a shift in the orientation of pharmaceutical services and the management of drugs as a commodity to comprehensive services (pharmaceutical care) in the sense of not only managing drugs but in a broader sense includes the implementation of providing information to support the correct and rational use of drugs, monitoring drug use to determine the final destination and the possibility of medication errors (Ministry of Health, 2014).